A cross-sectional study of travel patterns of older adults in the USA during 2015: implications for mobility and traffic safety. Issue 8 (11th August 2017) - Shen, Sijun; Koech, Wilson; Feng, Jing; Rice, Thomas M; Zhu, Motao
Abstract : Background: With an ever increasing population of older adults (65+ years) in the USA, a better understanding of this population's travel patterns is needed to improve travel mobility and transportation safety. Objective: In this study, we described the travel patterns of older adults in the USA during 2015. Methods: Travel patterns of older adults (65–74 and 75+ years) were compared with younger adults (25–64 years) by frequency and proportion of daily trips. The daily trips of various age groups were estimated using the 2015 American Time Use Survey. Results: The percentage of daily travellers was 88% for adults (25–64 years), 75% for adults (65–74 years) and 68% for adults (75+ years). While the percentage of privately owned vehicle (POV) drivers and average time of driving POVs decreased, the percentage of POV passengers increased as adults aged. Females were less likely to drive POVs and had decreased average daily driving time, but they were more likely to ride in POVs as passengers and had longer average daily riding times than their male counterparts across all age groups. Older adults were more likely to travel in the mornings and early afternoons (from 8:00 to 15:59) while younger adults were more likely to travel in the late afternoons and early evenings (from 16:00 to 19:59). Conclusions: POV use is the predominant mode of transit in the USA. As adults age, the percentages of daily travellers and POV drivers decrease. This pattern is more apparent among females than males. This study delineated travel patterns of older adults using a 2015 national survey, and the findings facilitate traffic systems designers and policy-makers to develop and implement initiatives to accommodate older adults' mobility needs and improve traffic safety.